The Effect of General Anesthesia on the Outcome of Root Canal Treatment in Pediatric Patients-A Retrospective Cohort Study - Shlomo Elbahary; Eyal Rosen; Sohad Haj-Yahya; Maysa Ghrayeb Elias; Shany Talmi; Igor Tsesis; Hagay Slutzky (MDPI AG, 2023)
This study aimed to evaluate the effect of general anesthesia (GA) on the 1-year outcome of Root Canal Treatment (RCT) performed in pediatric patients and to compare it to the outcome of RCT in pediatric patients without GA. Patients admitted for RCT in permanent dentition in a public hospital, dated 2015 to 2020, age 8-15 with a minimum of one year follow-up period, were included in the study. The sample consisted of 326 teeth from 269 patients treated by a single operator, with a recall rate of 81%. Overall, 124 teeth were treated under GA and 142 teeth were without GA. The mean follow-up time was 31.5 months. Data underwent statistical analysis and the significance threshold was set for p < 0.05. Of the total cases, 90% showed favorable outcomes. A significantly higher favorable outcome was seen in the GA group than in the non-GA group (98% and 85%, respectively, p < 0.001). The outcome was significantly affected by the type and quality of the coronal restoration, degree of root development, and lesion size (p < 0.05). According to the current study, in uncooperative pediatric patients, a more favorable outcome of root canal treatment can be obtained under GA than LA if the procedure is carried out with immediate restoration.